Systemic-to-Pulmonary Collateral Flow, as Measured by Cardiac Magnetic Resonance Imaging, Is Associated With Acute Post-Fontan Clinical Outcomes - Andrew C. Glatz; Jonathan J. Rome; Adam Small; Matthew J. Gillespie; Yoav Dori; Matthew Harris; Marc S. Keller; Mark A. Fogel; Kevin K. Whitehead (2012)
Systemic-pulmonary collateral (SPC) flow occurs commonly in single ventricle patients after superior cavo-pulmonary connection, with unclear clinical significance. We sought to evaluate the association between SPC flow and acute post-Fontan clinical outcomes using a novel method of quantifying SPC flow by cardiac magnetic resonance (CMR) imaging.All patients who had SPC flow quantified by CMR imaging before Fontan were retrospectively reviewed to assess for acute clinical outcomes after Fontan completion. Forty-four subjects were included who had Fontan completion between May 2008 and September 2010. SPC flow prior to Fontan measured 1.5±0.9 L/min/m(2), accounting for 31±11% of total aortic flow and 44±15% of total pulmonary venous flow. There was a significant linear association between natural log-transformed duration of hospitalization and SPC flow as a proportion of total aortic (rho=0.31, P=0.04) and total pulmonary venous flow (rho=0.29, P=0.05). After adjustment for Fontan type and presence of a fenestration, absolute SPC flow was significantly associated with hospital duration ≥7 days (odds ratio [OR]=9.2, P=0.02) and chest tube duration ≥10 days (OR=22.7, P=0.009). Similar associations exist for SPC flow as a percentage of total aortic (OR=1.09, P=0.048 for hospitalization ≥7 days; OR=1.24, P=0.007 for chest tube duration ≥10 days) and total pulmonary venous flow (OR=1.07, P=0.048 for hospitalization ≥7 days; OR=1.18, P=0.006 for chest tube duration ≥10 days).Increasing SPC flow before Fontan, as measured by CMR imaging, is associated with increased duration of hospitalization and chest tube following Fontan completion.